Bruchmechanische Untersuchung der Titan‐PEEK‐Grenzfläche in thermoplastischen Titan‐CF/PEEK‐Laminaten durch Mixed‐Mode‐Bending‐Versuche. Issue 6 (June 2014) - Schulze, K.; Hausmann, J.; Heilmann, S.; Wielage, B.
<x xml:space="preserve">Abstract</x> The adhesion and failure mechanism at well‐designed titanium‐PEEK interfaces within Ti‐CF/PEEK laminates are investigated by superposed mode I‐ and mode II‐loading before and after hydrothermal aging. The laser‐induced columnar structured oxide layer enhances the adhesion at the Titanium‐PEEK interface. PEEK‐Polymer that is locked mechanically in the capillary gaps of the columnar oxide structure are stretched and stiffed in the case of loading resulting in good adhesion. The adhesion at the oxide structure reduces by the influence of hydrothermal aging. Basically, the failure mechanism is not changed. Thus, the columnar oxide structure leads to enhanced humidity resistance of the adhesion between titanium and PEEK. The PEEK‐Polymer is also locked in the undercuts between the depressions and rims of the laser‐induced dot‐like surface structure resulting in adhesion. The adhesion at the dot‐like structured surface is nearly completely reduced by the influence of hydrothermal aging. The failure mechanism is changed from ductile failure within the PEEK‐Polymer to party disrupted rims and melt spatter.